Driving digital strategy a guide to reimagining your business - Gupta, Sunil 1958- (Boston, Massachusetts Harvard Business Review Press, 2018)
Digital transformation is no longer news. It is a necessity. Sunil Gupta, head of the digital transformation practice at Harvard Business School, provides a framework for large organizations to think through where and how to begin their transformation. Traditional boundaries of industries no longer define competition; businesses have to deal with partners who are both friends and enemies; competitive advantage does not come from low-cost or product differentiation strategies; how companies create and capture value is dramatically changing. This book shows how to rethink the four fundamental pillars of business to reinvent business for this new world. Business leaders, Gupta argues, need to reexamine four fundamental aspects of their business to thrive in the digital era--their business strategy, their value chain, their customers, and their organization. The book addresses questions that arise as companies navigate through this transition and provides a road map for this transformation. Filled with rich case studies and deep analysis, it shows how established firms can mitigate the threat as well as leverage the opportunities in the digital era.--Provided by publisher.
Introduction: Framework for reinventing your business -- Part One. Re-imagine your business: Business scope -- Business model -- Platforms and ecosystems -- Part Two. Re-evaluate your value chain: Rethinking R&D and innovation -- Operational excellence -- Omnichannel strategy -- Part Three. Re-connect with customers: Acquiring customers -- Engaging consumers -- Measuring and optimizing marketing spend -- Part Four. Re-build your organization: Managing digital transition -- Designing an organization for innovation -- Skills, capability, and talent management.
Includes bibliographical references and index.
donated by The Asia Foundation (Books for Asia)
Keywords: Business planning; Strategic planning; Technological innovations